"The two voices, " or more? Music and gender from myth and conquests to the neurosciences. Issue 5 (27th March 2023) - Majno, Maria
Abstract: Music is a unique phenomenon, constantly eliciting interest from a variety of viewpoints, several of which intersect the universal trait of musicality with sex/gender studies and the neurosciences. Its unparalleled power and physical, social, aesthetic, as well as cognitive, emotional and clinical ramifications make it a specially promising terrain for studies and reflections on sex and gender differences and their impact. This overview wishes to enhance awareness of such issues, also fostering an interdisciplinary exchange between the natural sciences, the humanities, and the arts. Over the centuries, different associations of music with the feminine gender have contributed to a pendulum between progressive recognition and stereotypical setbacks requiring to be overcome. Against this backdrop, music‐related neurophysiological and psychological studies on sex and gender specificities are reviewed in their multiple approaches and results, exposing or questioning differences in structural, auditory, hormonal, cognitive, and behavioral areas, also in relation to abilities, treatment, and pedagogy. Thus, the bridging potential of music as universal yet diverse language, art, and practice, recommends its gender‐aware integration into education, protective endeavors, and therapeutic interventions, to promote equality and well‐being.